Demystifying Poverty Measurement in Vietnam - Demombynes, Gabriel; Hoang Vu, Linh (World Bank Group, Washington, DC, 2015)
This paper provides an overview of poverty measurement issues in Vietnam for the non-specialist. Vietnam has two main approaches to measuring poverty. An income-based approach is used by the Ministry of Labor, Invalids, and Social Affairs to generate a classification used for determining anti-poverty program eligibility as well as poverty monitoring over the short term. A separate consumption-based approach has been used by the General Statistics Office and the World Bank (GSO-WB), principally to examine poverty changes over the longer run. These national poverty lines are distinct from the $1.25-a-day and $2-a-day international poverty lines. Vietnam s GSO-WB national poverty line is similar in purchasing power parity terms to that of other countries with similar levels of development. Simple projections of poverty rates through 2020 imply that the GSO-WB poverty rate will fall from a 2012 level of 17.2 percent to below 10 percent by 2020, and that over a third of ethnic minorities will still be poor despite large poverty reduction gains.